2001
DOI: 10.2165/00019053-200119070-00005
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Becaplermin in the Treatment of Diabetic Foot Ulcers in Four European Countries

Abstract: Becaplermin may be a cost-effective treatment for neuropathic diabetic foot ulcers in a wide range of European settings. In Sweden, Switzerland and the UK, becaplermin may even be cost saving. Substantial intercountry differences in resource patterns appear, at least partly, to be the logical outcome of differences in unit costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 10 publications
0
33
0
Order By: Relevance
“…39,40,42,52,53 Becaplermin as an adjunct to GWC has yielded favorable cost-effectiveness ratios in Canada, 39 France, 40 Sweden, 40,52 Switzerland, 40 the United Kingdom, 40 and the United States. 42,53,54 Studies inside and outside the United States have found that treatment with becaplermin has resulted in additional ulcer-free days and weeks and reduced long-term expenses, including office visits, dressings, recurrence rates, and amputation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39,40,42,52,53 Becaplermin as an adjunct to GWC has yielded favorable cost-effectiveness ratios in Canada, 39 France, 40 Sweden, 40,52 Switzerland, 40 the United Kingdom, 40 and the United States. 42,53,54 Studies inside and outside the United States have found that treatment with becaplermin has resulted in additional ulcer-free days and weeks and reduced long-term expenses, including office visits, dressings, recurrence rates, and amputation.…”
Section: Discussionmentioning
confidence: 99%
“…Costeffectiveness studies on the direct cost of care for DFU therapy included healing as the only primary outcome and did not include other potential surrogate endpoints, such as cost per cm 2 of WSA reduction. 39,40 Previous work by Margolis et al 41 found that percentage change in WSA can be used as a surrogate marker for complete wound healing. Access to health economic data will enable physicians and health-care decision makers in the United States to make better informed choices about treating DFUs.…”
Section: Platelet-derived Growth Factors and Wound Healingmentioning
confidence: 98%
“…In common with the industry submission, the results of Ghatnekar et al (2001) 247 are used for the costs of complications associated with uninfected ulcers, infected ulcers and gangrene, which, in 2006 prices, equate to event costs of £1643, £1684 and £2700, respectively. Again, these are slightly higher than those of the industry submission, probably due to different inflation rates having been assumed.…”
Section: Costs Of Complicationsmentioning
confidence: 99%
“…102 Baseline probabilities were taken from a prospective study of 183 patients and becaplermin efficacy was based on 20-week healing rates in a meta-analysis of clinical trials with 449 patients. Country-specific economic data, established through expert opinion, were integrated into the model to generate cost-effectiveness ratios.…”
Section: Empirical Analyses Of Geographical Variability In Modelling mentioning
confidence: 99%